A three level multi-period multi-location and multi-crop sustainable supply chain model - Quadra, Patricia Rovie B. (Animo Repository, 2009)
Agriculture worldwide has come to use increasing amounts of chemical pesticides and synthetic fertilizers and methods that are not sustainable which results to unbalanced crop rotation, pollution of crops and plants' impaired ability to absorb nutrients, thus lowering yield. Therefore, a three level multi period, multi-location and multi-crop sustainable supply chain model is formulated comprising of the resource, production and distribution level. The objective is to minimize the total cost of the system. The model was solved using General Algebraic Mathematical Model (GAMS). ©2009 IEEE.